(untitled) (Fractal: Journal of Psychology, 2013)
This paper presents and studies the first translation to Portuguese of “Methods for investigating concepts” (1928), by LS Sakharov, classic text of cultural-historical psychology. The article was organized in four parts, explaining: translation problems; the relationship between the author and his time; discussion of methods for investigating concepts/giftedness; the object, material and investigation procedures developed by Sakharov in relation with Vygotsky´s work. We also discuss the criticism, replication, and impact of the functional method of double stimulation (or method of Sakharov), presented in the translation.